Integrasi Nilai Pendidikan Islam dengan Budaya Jawa dalam Perspektif Emha Ainun Nadjib - Ahmad Solihin; Muhammad Azmi Al-Farisi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This study explores the idea of ​​integration between Islamic educational values ​​and Javanese culture according to Emha Ainun Nadjib through an analysis of his works. This study includes a library research study using a qualitative descriptive method with a character approach. Data sources were obtained from: interviews with figures (Cak Nun) and his biological child (Sabrang MDP), as well as an inventory of his thoughts in the form of books, the CakNun.com YouTube channel which is directly managed by Rumah Maiyah and Kiai Kanjeng. The results of the study show that Javanese cultural values ​​and educational values ​​according to Cak Nun Islam's view are almost incompatible with each other. The verse of the Qur'an which reads